Merawat Identitas Lokal melalui Bahasa Indonesia : Integrasi Teks Adat Maumere dalam Pembelajaran Akademik - Stevania Deko; Fahera Hasan; Yeremias Bardi (Jurnal Kajian Ilmu Pendidikan, Bahasa dan Komunikasi, 2026)
Indonesian language education plays a strategic role in strengthening national identity and preserving cultural values amid the pressures of globalization. In the global era, the dominance of foreign languages, digital media, and transnational cultures poses challenges to the existence of national languages and local cultural identities. This study aims to analyze the role of Indonesian language education as an instrument for reinforcing national identity and cultural awareness in formal educational settings. The research employs a qualitative descriptive method with a literature review approach, examining scientific journals, policy documents, and relevant educational studies published within the last five years. Data were analyzed through content analysis to identify patterns, themes, and conceptual relationships related to language education and cultural identity. The findings reveal that Indonesian language education not only functions as a medium of communication but also serves as a vehicle for transmitting national values, cultural narratives, and collective identity. Learning materials that integrate local wisdom, literature, and cultural texts significantly contribute to students’ cultural awareness and national character development. Furthermore, Indonesian language education plays an important role in fostering critical literacy, cultural resilience, and a sense of belonging among learners in a globalized context. The study implies that strengthening Indonesian language education through curriculum development, contextual learning, and teacher competence enhancement is essential to sustaining national identity and cultural continuity in the era of globalization.